PENERAPAN RHYTHMIC MOVEMENT TRAINING DALAM MENINGKATKAN ATENSI PADA ANAK DENGAN ATTENTION-DEFICIT/HYPERACTIVITY DISORDER - Said, Aprillia Ramadhin; Marat, Samsunuwiyati; Basaria, Debora (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
The number of children diagnosed with Attention-Deficit / Hyperactivity Disorder (ADHD) keeps increasing, therefore it is important to highlight the problems experienced by children with ADHD. The problem that persists as children with ADHD grow older is attention problem. Attention problem can impair learning, performance, academic achievement and social functioning. Attention problem among ADHD children is closely related to the condition of retained primitive reflex. This attention problem must be solved to minimize the ensuing impact, especially among children with ADHD. There are several therapies to help children with ADHD overcome attention problem, one of them being Rhythmic Movement Training. Rhythmic Movements Training (RMT) integrates retained primitive reflexes through movements that can stimulate the development of nerve cells in the brain, which results in increased attention. The purpose of this study is to determine the application of Rhythmic Movement Training (RMT) in increasing attention of children with ADHD. This study uses one group pre-test post-test design using Structured Observation of Academic and Play Settings (SOAPS) to measure the attention of participants before and after Rhythmic Movement Training (RMT) is given. The results show that Rhythmic Movement Training (RMT) can increase the attention of participants, who are children with ADHD. Jumlah anak dengan Attention-Deficit/Hyperactivity Disorder (ADHD) semakin bertambah, sedangkan terdapat beberapa permasalahan yang dialami oleh anak dengan ADHD. Permasalahan yang menetap seiring dengan perkembangan usia pada anak dengan ADHD adalah permasalahan atensi. Permasalahan atensi dapat menyebabkan permasalahan dalam pembelajaran, performa anak, prestasi akademik dan fungsi sosial. Permasalahan atensi pada anak ADHD erat kaitannya dengan kondisi retained primitive reflex. Permasalahan atensi ini perlu diatasi untuk meminimalisir dampak yang terjadi, khususnya pada anak dengan ADHD. Terdapat beberapa terapi untuk mengatasi permasalahan atensi pada anak dengan ADHD, salah satunya dengan Rhythmic Movement Training. Rhythmic Movements Training (RMT) dapat mengintegrasikan retained primitive reflex melalui gerakan yang dapat menstimulasi perkembangan sel saraf pada otak, yang dapat berdampak pada meningkatnya atensi. Tujuan penelitian ini adalah untuk mengetahui penerapan Rhythmic Movement Training (RMT) dalam meningkatkan atensi pada anak ADHD. Penelitian ini menggunakan one group pre-test post-test design dengan menggunakan Structured Observation of Academic and Play Settings (SOAPS), untuk mengukur atensi para partisipan sebelum dan sesudah diberikannya Rhythmic Movement Training (RMT). Hasil menunjukkan bahwa Rhythmic Movement Training (RMT) dapat meningkatkan atensi para partisipan yang merupakan anak dengan ADHD.